2010
DOI: 10.1007/s12665-010-0584-5
|View full text |Cite
|
Sign up to set email alerts
|

The study of metal contamination in urban topsoils of Mexico City using GIS

Abstract: This research presents and discusses information concerning the spatial distribution of heavy metals (Pb, Cu, Zn, Ba, Co, Cr, Ni and V) in the urban environments of Mexico City using geographical information system and statistical analysis. Superficial soil samples (n = 146) were analyzed. The highest contamination indices were found in the north and center zone of the metropolitan area. In contrast, the surrounding rural fields show a lower impact grade. The higher concentrations of Pb, Cu, Zn and Ba were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 29 publications
4
20
0
3
Order By: Relevance
“…Un plan de saneamiento debe instrumentarse para esos lugares, ya que el V es un elemento que si se inhala o ingiere vía oral o por contacto vía dermis, es causal de cáncer, afecta la reproducción y es bioacumulativo (Méndez, Báez, & Patricia, 2014;Rodríguez-Mercado & Altamirano-Lozano, 2006). …”
Section: Distribución Espacial De Los Metales Pesadosunclassified
See 1 more Smart Citation
“…Un plan de saneamiento debe instrumentarse para esos lugares, ya que el V es un elemento que si se inhala o ingiere vía oral o por contacto vía dermis, es causal de cáncer, afecta la reproducción y es bioacumulativo (Méndez, Báez, & Patricia, 2014;Rodríguez-Mercado & Altamirano-Lozano, 2006). …”
Section: Distribución Espacial De Los Metales Pesadosunclassified
“…A sanitation plan should be implemented for these places, since V is an element that if it is inhaled or ingested orally or direct person-to-person via the dermis, causes cancer, affects reproduction and is bioaccumulative (Méndez, Báez, & Patricia, 2014;Rodríguez-Mercado & Altamirano-Lozano, 2006).…”
Section: Distribución Espacial De Los Metales Pesadosmentioning
confidence: 99%
“…These differences may be related to the city size and industrial activities; however, similar metal contents have been reported in top soils in Mexico City (Rodríguez-Salazar et al 2011), which is the largest city in the country.…”
Section: Metal Concentrations In Urban Dustmentioning
confidence: 56%
“…In the case of Pb, only two samples of road dust yielded values above the recommended limit (400 mg kg -1 ); both samples correspond to high-traffic areas. According to Del Rio-Salas et al (2012) and Rodríguez-Salazar et al (2011), Pb isotopic ratios suggest pollution by Pb in gasoline. In Mexico, using Pb as a gasoline additive has been prohibited since 1987; however, a recent study suggests a mixing of Pb isotopic signatures from leaded gasoline and urban dust.…”
Section: Metal Concentrations In Urban Dustmentioning
confidence: 99%
See 1 more Smart Citation